138k views
3 votes
Write 6(x – 5)4 + 4(x – 5)2 + 6 = 0 in the form of a quadratic by using substitution.

A. 6u2 + 4u + 6 = 0, where u = x – 5
B. 6u2 + 4u + 6 = 0, where u = (x – 5)2
C. 6u4 + 4u + 6 = 0, where u = x – 5
D. 6u4 + 4u + 6 = 0, where u = (x – 5)2

2 Answers

4 votes

Answer:

B

Explanation:

User Arne Stockmans
by
5.2k points
4 votes

We are given the equation:


6(x-5)^(4)+4(x-5)^(2)+6=0..........(1)

Now we have to write it in quadratic form using substitution.

The general form of quadratic equation is given by:


ax^(2)+bx+c=0

So let us say


(x-5)^(2)=u.......(2)

Plugging the value of (x-5)² from equation (2) in (1),


6u^(2)+4u+6=0

Answer : Option B.
6u^(2)+4u+6=0


User Walter Cejas
by
5.5k points